Did the extraordinary appeal to the Extraordinary Court fulfill its objectives? - Domańska, Aldona (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
An extraordinary appeal is a new procedural instrument that has been in operation in the Polish legal system since April 3, 2018. Already at the stage of discussions on the amendment to the Act on the Supreme Court, which also included provisions on the extraordinary appeal, it caused extreme emotions. Despite two years of operation, it is not unequivocally assessed by representatives of the doctrine or practitioners. The publication is devoted exclusively to procedural aspects, problems related to the lodging of a complaint. The author tries to answer the question whether, from this point of view, the complaint fulfills the indicated function. The postulate that its application should be statutorily limited to a very narrow category of cases in which the ruling violated the legitimate interests of individuals, and the possible correction of the ruling will not lead to violation of the rights of other people, seems right. It is necessary to specify the conditions for lodging a complaint, which has been shown to be imprecise and of assessment.